2017
DOI: 10.1002/mgg3.293
|View full text |Cite
|
Sign up to set email alerts
|

A strategy for molecular diagnostics of Fanconi anemia in Brazilian patients

Abstract: BackgroundFanconi anemia (FA) is a predominantly autosomal recessive disease with wide genetic heterogeneity resulting from mutations in several DNA repair pathway genes. To date, 21 genetic subtypes have been identified. We aimed to identify the FA genetic subtypes in the Brazilian population and to develop a strategy for molecular diagnosis applicable to routine clinical use.MethodsWe screened 255 patients from Hospital de Clínicas, Universidade Federal do Paraná for 11 common FA gene mutations. Further anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 66 publications
0
13
0
1
Order By: Relevance
“…Our results showed large intragenic deletions as the most frequent mutations found in homozygous and heterozygous states in 55.17% of the patients. This frequency is higher than that observed in other populations [31.25% in India (Solanki et al, 2016); 25% in Brazilian patients (Pilonetto et al, 2017)]. A meta-analysis has shown that between 15 and 40% of pathogenic mutations in FANCA are caused by large deletions (Ameziane et al, 2012;Gille et al, 2012).…”
Section: Discussionmentioning
confidence: 65%
“…Our results showed large intragenic deletions as the most frequent mutations found in homozygous and heterozygous states in 55.17% of the patients. This frequency is higher than that observed in other populations [31.25% in India (Solanki et al, 2016); 25% in Brazilian patients (Pilonetto et al, 2017)]. A meta-analysis has shown that between 15 and 40% of pathogenic mutations in FANCA are caused by large deletions (Ameziane et al, 2012;Gille et al, 2012).…”
Section: Discussionmentioning
confidence: 65%
“…The subsequent identification of the mutation in our patient will allow us to verify the genetic-phenotypic correlation as well as the prognosis. A strategy for the molecular investigation based on an initial screening for common mutations in the most frequently affected genes FANCA, FANCC, and FANCG as done in Brazil [16] could reduce the cost of genetic testing and therefore be more accessible in our countries.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible to use massive parallel sequencing and multiplex ligation-dependent probe amplification based genotyping methods to detect pathogenic variants in any of the 22 genes associated with the FA phenotype. [46][47][48] Due to the high complexity of the disease and its multisystemic involvement, all patients confirmed to have FA should be referred to health institutions where they can receive an integral and interdisciplinary management.…”
Section: Diagnostic Confirmation Of Fanconi Anemiamentioning
confidence: 99%
“…[9][10][11] Finally, amplificación múltiple de sondas dependiente de ligamiento (MLPA por sus siglas en inglés) para la detección de variantes patogénicas en alguno de los 22 genes asociados con el fenotipo de la anemia de Fanconi. [46][47][48] Debido a la alta complejidad de la enfermedad y a la afectación multisistémica, todos los pacientes deben enviarse a instituciones de tercer nivel de atención, para que reciban tratamiento interdisciplinario e integral.…”
Section: Introductionunclassified